К распространению некоторых наиболее вредных видов рода Apion Нгbst. (Curculionidae) в Дагестане - Солодовникова, B.C (Вестник зоологии, 1974)
63 species of the genus Apion were registered first for Daghestan, 16 of them are new in the entomofauna of the entire Caucasus. Only 30% of the spcies occurred in all natural area. The fauna of Curculionidae from the genus Apion is the richest in the region of foothills and montane belt in the open areas (in mountain meadows and steppes). In the lowland mesophyllous fauna of the genus Apion is weakly developed, with the exception of A. aeneicolle Gers t.— semi-desert xerophil of the Middle Asian origin (found in mass quantity). Almost 32% of species are pests of wild and cultivated grasses from the families Leguminosae, Malvaceae, Compositae, etc.